16 people. Divide 97 by 6 and you get 16.16 but you can’t send a message to a .16 of a person so it’s just 16 people.
Answer:
11 meters
Step-by-step explanation:
Lets say that w = width of the rectangle, to start. If the length of the rectangle is 3 meters greater than 2 times the width, the length of the rectangle is equal to 3 + 2w.
The perimeter of the rectangle is 2 * length of rectangle + 2 * width of the rectangle. With the perimeter being equal to 30 and width being w and length being 2w+3:
The perimeter of the rectangle is 2(w) + 2(2w+3) = 30.
We first need to find out w first, which will give us the width of the rectangle. Taking it step by step, we get:
2w + 4w + 6 = 30
6w + 6= 30
6w = 24 which is done by subtracting both sides by 6 to put the variables on one side and the values on the other side
w = 4 which is done by dividing 6 on both sides
Ultimately, this gets width to be 4 meters. Now that we found the width, we need to plug w = 4 into the equation we set up for length which is 2w+3.
That being said, the ANSWER is:
length of rectangle = 2(4)+3 = 11 meters
Hope this helps! :)
1 triangle: 2*6 + 1*5
2 triangles: 2*6 + 2*5
3 triangles: 2*6 + 3*5
So for n triangles: p = 2*6 + n*5 = 12 + 5n
<u>Answer-</u>
The % error of this approximation is 1.64%
<u>Solution-</u>
Here,
![\Rightarrow f(x) = 2\cos x + e^{2x}](https://tex.z-dn.net/?f=%5CRightarrow%20f%28x%29%20%3D%202%5Ccos%20x%20%2B%20e%5E%7B2x%7D)
![\Rightarrow f'(x) = -2\sin x + 2e^{2x}](https://tex.z-dn.net/?f=%5CRightarrow%20f%27%28x%29%20%3D%20-2%5Csin%20x%20%2B%202e%5E%7B2x%7D)
And,
![\Rightarrow f(2) = 2\cos 2 + e^{4}](https://tex.z-dn.net/?f=%5CRightarrow%20f%282%29%20%3D%202%5Ccos%202%20%2B%20e%5E%7B4%7D)
![\Rightarrow f'(2) = -2\sin 2 + 2e^{4}](https://tex.z-dn.net/?f=%5CRightarrow%20f%27%282%29%20%3D%20-2%5Csin%202%20%2B%202e%5E%7B4%7D)
Taking (2, f(2)) as a point and slope as, f'(2), the function would be,
![\Rightarrow y-y_1=m(x-x_1)](https://tex.z-dn.net/?f=%5CRightarrow%20y-y_1%3Dm%28x-x_1%29)
![\Rightarrow y-(2\cos 2 + e^{4})=(-2\sin 2 + 2e^{4})(x-2)](https://tex.z-dn.net/?f=%5CRightarrow%20y-%282%5Ccos%202%20%2B%20e%5E%7B4%7D%29%3D%28-2%5Csin%202%20%2B%202e%5E%7B4%7D%29%28x-2%29)
![\Rightarrow y=(-2\sin 2 + 2e^{4})(x-2)+(2\cos 2 + e^{4})](https://tex.z-dn.net/?f=%5CRightarrow%20y%3D%28-2%5Csin%202%20%2B%202e%5E%7B4%7D%29%28x-2%29%2B%282%5Ccos%202%20%2B%20e%5E%7B4%7D%29)
The value of f(2.1) will be
![\Rightarrow y=(-2\sin 2 + 2e^{4})(2.1-2)+(2\cos 2 + e^{4})](https://tex.z-dn.net/?f=%5CRightarrow%20y%3D%28-2%5Csin%202%20%2B%202e%5E%7B4%7D%29%282.1-2%29%2B%282%5Ccos%202%20%2B%20e%5E%7B4%7D%29)
![\Rightarrow y=(-2\sin 2 + 2e^{4})(0.1)+(2\cos 2 + e^{4})](https://tex.z-dn.net/?f=%5CRightarrow%20y%3D%28-2%5Csin%202%20%2B%202e%5E%7B4%7D%29%280.1%29%2B%282%5Ccos%202%20%2B%20e%5E%7B4%7D%29)
![\Rightarrow y=64.5946](https://tex.z-dn.net/?f=%5CRightarrow%20y%3D64.5946)
According to given function, f(2.1) will be,
![\Rightarrow f(2.1) = 2\cos 2.1 + e^{2(2.1)}](https://tex.z-dn.net/?f=%5CRightarrow%20f%282.1%29%20%3D%202%5Ccos%202.1%20%2B%20e%5E%7B2%282.1%29%7D)
![\Rightarrow f(2.1) = 65.6766](https://tex.z-dn.net/?f=%5CRightarrow%20f%282.1%29%20%3D%2065.6766)
![\therefore \%\ error=\dfrac{65.6766-64.5946}{65.6766}=0.0164=1.64\%](https://tex.z-dn.net/?f=%5Ctherefore%20%5C%25%5C%20error%3D%5Cdfrac%7B65.6766-64.5946%7D%7B65.6766%7D%3D0.0164%3D1.64%5C%25)